2021
DOI: 10.1192/bja.2021.69
|View full text |Cite
|
Sign up to set email alerts
|

Domestic abuse and mental health: the amplified risks created during the pandemic

Abstract: SUMMARY No recent pandemic has had such a severe socioeconomic impact as COVID-19. Significant economic uncertainty and social restrictions have led to increased levels of stress for many. There has been increased social isolation, financial stress and alcohol intake, all of which can increase domestic abuse and other forms of household abuse. Increases in abuse in the home found in other public health emergencies and economic recessions can be seen now – reported UK domestic abuse rates have increased sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022). Ecological models can also take wider social factors into account, linking immediate familial risk factors with the poverty, mental health problems and substance misuse problems that underpin family and community level violence (Hisham et al, 2021). Julie below illustrates the importance of these wider factors that influence mother-child relational development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022). Ecological models can also take wider social factors into account, linking immediate familial risk factors with the poverty, mental health problems and substance misuse problems that underpin family and community level violence (Hisham et al, 2021). Julie below illustrates the importance of these wider factors that influence mother-child relational development.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review found evidence to support the use of family therapy in the reduction of IPV (Stith et al, 2022). Ecological models can also take wider social factors into account, linking immediate familial risk factors with the poverty, mental health problems and substance misuse problems that underpin family and community level violence (Hisham et al, 2021). Julie below illustrates the importance of these wider factors that influence mother-child relational development.“Through my pregnancy I was still drinking cos I thought that it would go away (laughs) and I didn’t tell my mum and dad and I was just messed up you know mentally and I think from postnatal depression from (older sons name) and all the stuff that had gone wrong with (older sons name) and (sons name) dad I just didn’t want to believe I was pregnant.” Julie…”
Section: Resultsmentioning
confidence: 99%
“…Individuals known to mental health services are disproportionately affected by domestic violence and abuse and the COVID-19 pandemic may have exacerbated the risk factors for violence and abuse to which this population are exposed. Hisham et al (2022, this issue) consider how mental health professionals can reduce exposure to these modifiable factors during the pandemic among their patients.…”
mentioning
confidence: 99%